Hydroxylase inhibition regulates inflammation-induced intestinal fibrosis through the suppression of ERK-mediated TGF-β1 signaling - Manresa, Mario C.; Tambuwala, Murtaza M.; Radhakrishnan, Praveen; Harnoß, Jonathan M.; Brown, Eric; Cavadas, Miguel A.; Keogh, Ciara E.; Cheong, Alex; Barrett, Kim E.; Cummins, Eoin P.; Schneider, Martin; Taylor, Cormac T. (American journal of physiology. Gastrointestinal and liver physiology, 2016)
Fibrosis is a complication of chronic inflammatory disorders such as inflammatory bowel disease, a condition which has limited therapeutic options and often requires surgical intervention. Pharmacologic inhibition of oxygen-sensing prolyl hydroxylases, which confer oxygen sensitivity upon the hypoxia-inducible factor pathway, has recently been shown to have therapeutic potential in colitis, although the mechanisms involved remain unclear. Here, we investigated the impact of hydroxylase inhibition on inflammation-driven fibrosis in a murine colitis model. Mice exposed to dextran sodium sulfate, followed by a period of recovery, developed intestinal fibrosis characterized by alterations in the pattern of collagen deposition and infiltration of activated fibroblasts. Treatment with the hydroxylase inhibitor dimethyloxalylglycine ameliorated fibrosis. TGF-β1 is a key regulator of fibrosis that acts through the activation of fibroblasts. Hydroxylase inhibition reduced TGF-β1-induced expression of fibrotic markers in cultured fibroblasts, suggesting a direct role for hydroxylases in TGF-β1 signaling. This was at least in part due to inhibition of noncanonical activation of extracellular signal-regulated kinase (ERK) signaling. In summary, pharmacologic hydroxylase inhibition ameliorates intestinal fibrosis through suppression of TGF-β1-dependent ERK activation in fibroblasts. We hypothesize that in addition to previously reported immunosupressive effects, hydroxylase inhibitors independently suppress profibrotic pathways.
Gesehen am 07.05.2020